Effects of Digging Substrate on Growth and Fur in Blue Versus Shadow Type of Alopex lagopus - Korhonen, HT; Huuki, H (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2011)
Abstract. Our study sought to establish the extent to which digging substrate in the cage affects growth performance and fur properties in farmed foxes (Alopex lagopus) of the shadow white and blue colour types. The plates were on either the wall or the floor; the sandbox was always on the floor. A standard cage without any digging substrate was used as a control. There were 20 foxes in each group (one male and one female per cage). The cage setups were as follows: 1) a standard cage (105 cm long Ã 115 cm wide Ã 70 cm high) without digging substrates, which housed the control group; 2) a standard cage (105 cm long Ã 115 cm wide Ã 70 cm high) with a solid metal plate (210 Ã 297 mm) on the wall for digging and scratching; 3) a standard cage (105 cm long Ã 115 cm wide Ã 70 cm high) with a solid metal plate (210 Ã 297 mm) on the floor for digging and scratching; and 4) a standard cage (105 cm long Ã 115 cm wide Ã 70 cm high) with a metal sandbox for digging and scratching (80 Ã 40 Ã 14 cm, LÃWÃH). The sandbox had a 10 cm layer of sand (ca. 25 kg, particle size 0-18 mm) on the bottom. All animals grew well and reached normal body weights. No significant growth differences were found between blue and shadow types within the groups. Furthermore, skin length did not differ between colour types or between groups. Skin weight, on the other hand, was heavier in the blue than in the shadow type in the plate floor groups. No differences were recorded in the other groups. Fur quality was poorest in the blue type of the standard group and best in the shadow type of the plate wall group. Cover and mass were also best in the shadow type of the plate wall group. Furs were dirtiest in the sandbox groups, irrespective of colour type. Our findings tempt us to conclude that body growth is highly affected by digging substrate and that a sandbox in the cage causes the dirtiest fur and may, therefore, be avoided in farming practice.Key Words: Alopex lagopus, digging substrate, fur properties, growth performance, colour type